2009
DOI: 10.1097/rli.0b013e31818f76b5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gadolinium-Based Magnetic Resonance Imaging Contrast Agents on Human Skin in Organ Culture and Human Skin Fibroblasts

Abstract: These data provide evidence that GBCA exposure in ex vivo skin from healthy individuals increases fibroblast proliferation and has effects on the enzyme/inhibitor system that regulates collagen turnover in the skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
101
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 77 publications
(115 citation statements)
references
References 40 publications
13
101
1
Order By: Relevance
“…4. Dependent edema/fluid overload leading to enhanced exposure of interstitial tissue to GBCA in vivo (6) accords with the observation that fibroblasts can elicit a profibrotic response to GBCA in vitro (40)(41)(42). …”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…4. Dependent edema/fluid overload leading to enhanced exposure of interstitial tissue to GBCA in vivo (6) accords with the observation that fibroblasts can elicit a profibrotic response to GBCA in vitro (40)(41)(42). …”
Section: Discussionsupporting
confidence: 60%
“…In a separate study, chelated Gd in the form of Omniscan, Magnevist, MultiHance, and ProHance all increased proliferation of human dermal fibroblasts in monolayer culture (41). Additionally, increased proliferation of cells was accompanied by an increase in production of matrix metalloproteinase-1 (MMP-1) and tissue inhibitor of matrix metalloproteinase-1 (TIMP-1) but no increase in type I procollagen (41,42). Specific analysis of the signaling events immediately after GBCA application shows activation of tyrosine kinases within minutes following GBCA exposure, again suggesting that chelated Gd could be acting as the trigger molecule (42).…”
Section: Effect Of Gbca On Fibroblastsmentioning
confidence: 88%
See 1 more Smart Citation
“…ligand itself without Gd 3þ did not induce skin lesions, and incubation with a ligand also did not induce fibroblast proliferation in vitro (11,16,25). These preclinical data suggest that neither skin lesions nor fibroblast proliferation are related to the presence of free ligand but are, instead, correlated with high Gd concentration in the skin.…”
Section: Potential Role Of Gbcas In Nsfmentioning
confidence: 88%
“…It has also been reported that GBCA exposure in ex vivo skin from healthy humans increases fibroblast proliferation and has effects on the enzyme/inhibitor system that regulates collagen turnover in the skin, in particular an activation of tissue inhibitor of metalloproteinase 1 (TIMP1) and matrix metalloproteinase-1 (MMP-1) (25). The researchers observed an inverse relationship between compound stability and concentration required to stimulate fibroblast responses (25). An in vitro activation of fibroblasts and peripheral blood monocytes by GBCAs have also been reported (26,27).…”
Section: Nsf Animal Modelsmentioning
confidence: 99%